Pemanfaatan Model Pembelajaran Cooperative Script untuk Meningkatkan Kemampuan Membaca Intensif Siswa di SMP 3 Bina Dharma Kota Bandung - Setiawan, Budi; Fuadah, Annisa Tsamratul; Selarashati, Anggun; N, Arrinda Windiana; Hasan, Muhammad Lutfi; Herniati, Siti Tasniah; Bardian, Soca Permana (CV. ITTC INDONESIA, 2024)
The purpose of this study was to improve students' intensive reading skills by applying the Cooperative Script model. This study used the Quasi Experimental Research method with the implementation procedure being a research method that was carried out without randomization, but involved placing participants into groups. This study used a quasi-experimental design with an experimental group and a control group. The experimental group was given learning using the Cooperative Script, while the control group used conventional learning methods. Data were collected through intensive reading tests before and after treatment. The results of the data analysis showed that there was a significant increase in students' intensive reading skills in the experimental group compared to the control group. This study shows that the Cooperative Script learning model is effective in improving students' intensive reading skills. This study provides important implications for teachers in choosing interactive and collaborative learning strategies to improve student learning outcomes. Keywords: Cooperative Script, Membaca intensif, Pembelajaran The purpose of this study was to improve students' intensive reading skills by applying the Cooperative Script model. This study used the Quasi Experimental Research method with the implementation procedure being a research method that was carried out without randomization, but involved placing participants into groups. This study used a quasi-experimental design with an experimental group and a control group. The experimental group was given learning using the Cooperative Script, while the control group used conventional learning methods. Data were collected through intensive reading tests before and after treatment. The results of the data analysis showed that there was a significant increase in students' intensive reading skills in the experimental group compared to the control group. This study shows that the Cooperative Script learning model is effective in improving students' intensive reading skills. This study provides important implications for teachers in choosing interactive and collaborative learning strategies to improve student learning outcomes.